Use of the Walking Impairment Questionnaire and Walking Estimated-Limitation Calculated by History questionnaire to detect maximal walking distance equal to or lower than 250 m in patients with lower extremity arterial disease - Tollenaere, Quentin; Métairie, Antoine; Le Pabic, Estelle; Le Faucheur, Alexis; Mahé, Guillaume (Frontiers in Cardiovascular Medicine, 2023)
Objective: The accuracy and optimal threshold of the Walking Impairment Questionnaire (WIQ) and the Walking Estimated-Limitation Calculated by History (WELCH) questionnaire to determine a maximal walking distance (MWD) below or equal to 250m has yet to be assessed. Methods: This retrospective study recruited 388 consecutive patients with suspected symptomatic Lower Extremity Artery Disease (LEAD). Collected data included patient’s history, rest Ankle Brachial Index, WIQ and WELCH. MWD was assessed with treadmill test at 2mph (3.2km/h) with a 10% grade. An optimized threshold was determined for each questionnaire by Receiver Operating Characteristic (ROC) curves to detect a MWD ≤250m. Then, multivariate analysis was performed to build a simple score to detect MWD≤250m. Results: The study included 297 patients (63±10 years old). With a threshold of ≤64%, the WIQ predicted a MWD ≤250m with an accuracy of 71.4% [66.2%; 76.5%]. With a threshold of ≤22, the WELCH predicted a treadmill walking distance ≤250m with an accuracy of 68.7% [63.4%; 74.0%]. A new score with only four “yes or no” questions had an accuracy of 71.4% [66.3%; 76.6%]. Conclusion: A WIQ ≤64% and a WELCH ≤22 help to predict a walking distance ≤250 meters on a treadmill test at 2mph (3.2km/h) with a 10% grade. A 4-item score could be used for quick evaluation of a LEAD patient’s walking distance but requires further confirmation studies.